Principal Leadership In Effort To Increase The Motivation Of The Teacher (A Case Study At Elementary School) - Wiwik Maladerita; Firnando Sabetra; Fris Okta Falma; Rusdinal; Nurhizrah Gistituati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This  study  aims  to  describe  the principal leadership in efforts to increase the motivation of the the teachers.  This study examines the influence of the principal's role as a leader on the motivation of elementary school teachers in Tapan District. The research method used ex-post facto with a quantitative approach and a correlational design. The results of simple linear regression analysis for testing hypothesis 2 obtained a partial correlation coefficient of X variable of 0.504 and is positive; Sig (2-tailed) of 0.000 is less than 0.05. Thus, it can be concluded that there is a positive correlation between the role of the principal as a leader, and the work motivation of teachers.